Pengaruh Pelapisan Kitosan terhadap Sifat Fisik dan Kimia Tomat Segar (Lycopersicum pyriforme) pada Berbagai Tingkat Kematangan - Melly Novita; Satriana Satriana; Martunis Martunis; Syarifah Rohaya; Etria Hasmarita (Agricultural Faculty, 2012)
Tomato fruit undergoes many physicochemical changes after harvest caused by the process of metabolism. The method used to inhibit the metabolic processes in tomatoes can be overcome by controlled atmosphere storage. However, this method requires a high cost. Therefore there is another method that is more practical and economical to imitate the mechanism of the controlled atmosphere is by the use of coating materials (coating). Coating material must be able to form a barrier layer of the loss of water content and can maintain fruit quality and does not pollute the environment. Chitosan is a natural alternative as a coating material that is non-toxic and safe for health. This study aimed to observe the effect of chitosan coating on quality and shelf life of fresh tomatoes at different maturity levels. The study design used was completely randomized design (CRD) factorial with two factors. The factor I was the maturity stages which consisted of 3 (three) levels : K1 = full green (0-10% red skin), K2 = light red (30-60% red skin), K3 = ripe ( 70% red skin). Factor II is storage duration which consisted of 5 (five) level : P1 = 0 day, P2 = 5 days, P3 = 10 days, P4 = 15 days, P5 = 20 days, with 2 (two) replications. The analysis conducted on tomatoes were weight loss, solusble solids concentration, total acid, and vitamin C. The results showed that the tomatoes were coated chitosan could inhibit weight loss, soluble solids concentration, total acid, and vitamin C than untreated tomatoes (control). Chitosan coating with a concentration of 1% and a long soaking for 10 minutes on the tomatoes with the maturity stages of 0-10% skin red and 30-60% skin red could maintain in good condition for 20 days of storage. But the tomatoes with the maturity stage 70% red skin only able to survive 10 days of storage.